Phylogenetic analyses of antibiotic-producing Streptomyces sp. isolates obtained from the stingless-bee Tetragonisca angustula (Apidae: Meliponini) - Cambronero Heinrichs, Juan Carlos (2019)
Many insects have been associated with actinobacteria in protective symbiosis where antimicrobial metabolites inhibit host pathogens. However, the microbiota of neotropical insects such as the stingless-bee Tetragonisca angustula is poorly explored. T. angustula is a meliponid bee widely distributed in Latin America, its honey is traditionally exploited because of its ethno-pharmacological properties and its antimicrobial activity has been demonstrated. Also, the well-structured nest of this species allows exploration of the microbiota of its different components. Even though Streptomyces spp. have been cultured from stingless-bees, little is known about their role in this insect–microbe relationship. In this study, we examined the association between culturable actinobacteria and T. angustula, and evaluated the isolates’ potential as antimicrobial producers. We isolated 51 actinobacteria from adult bees and different substrates of the hive of T. angustula (pollen and honey storage, garbage pellets and cerumen). We then performed a 16S rRNA phylogenetic analysis that clusters the bacteria to previously described lineages of host-associated Streptomyces. In addition, all the isolates were classified according to their antibacterial activity against human pathogens, measured by a growth inhibition test based on diffusion in agar. More than 50 % of our isolates exhibit antimicrobial activity, mainly to Gram-positive bacteria and fungi and only two against Gram-negative bacteria. Additionally, we obtained electron micrographs of adult bees with what appears to be patches of hyphae with Streptomyces-like cell morphology on their body surface. Our results suggest that T. angustula possibly uptakes and transfers actinobacteria from the environment, acting as vectors for these potentially beneficial organisms. This research provides new insights regarding the microbiota associated with T. angustula and justify future studies exploring the full diversity of the microbial community associated with the hive and the possible exchange of microbes with the crops they pollinate.